STUDI ANALISIS GANGGUAN PERANGKAT HUBUNG BAGI TEGANGAN RENDAH DAN UPAYA MENGATASINYA DI PLN AREA TANJUNG PRIOK - Redaksi Tim Jurnal (Sekolah Tinggi Teknik PLN, 2017)
Medium voltage feeders are a means for the distribution of electricity from substations to consumers. But in reality these feeders often experience interference, among other is interference onthe low voltage network, especiallyCircuit For Low Voltage Device. Circuit For Low Voltage Device (PHB-TR) is device used as a liaison, security, and dividers electrical power from an electric power source to the customer. Over time, the PHB-TR also decreased quality of service so that should be their efforts to overcome the problems in order to maintain or restore the initial achievement level and can operate with high reliability so that the continuity of the electrical service will be achieved. The disturbances that can occur in this PHB-TR as damage to the NH fuse, corona contained in ground plate, over current and damage to the measuring instrument.Additionally by overcoming the interference can secure the assets of PLN from the interferences and reduce the cost of replacing broken tools.